THE RELATIONSHIP BETWEEN STRESS LEVEL AND ANXIETY LEVEL WITH THE MENSTRUAL CYCLE OF GRADE XII STUDENTS OF METHODIST HIGH SCHOOL 1 MEDAN: THE RELATIONSHIP BETWEEN STRESS LEVEL AND ANXIETY LEVEL WITH THE MENSTRUAL CYCLE OF GRADE XII STUDENTS OF METHODIST HIGH SCHOOL 1 MEDAN - Fevi Yolanda Siagian (Jurnal Kedokteran Methodist, 2025)
Background : Stress is an individual's response to stress that can disrupt physical or psychological balance. Stress and anxiety play a role in disrupting the menstrual cycle, with cortisol as an indicator of stress levels. Research shows that stress and anxiety can affect menstrual irregularities, especially in adolescent girls who are prone to hormonal and emotional changes during puberty. Objective : To determine the relationship between stress levels and anxiety levels with menstrual cycles in grade XII students of SMA Methodist 1 Medan. Method : Type This research was conducted by descriptive correlation method with a Cross Sectional approach.Results: The results of this study showed that there was a significant relationship between stress level and menstrual cycle with a p value of < 0.05 and there was a significant relationship between anxiety level and menstrual cycle with a p value = 0.05.Conclusion : Based on the results of the research that has been carried out, it can be concluded that in grade XII students of SMA Methodist I Medan, there is a significant relationship between the level of anxiety and stress with the menstrual cycle. Keywords : Stress, Anxiety, Menstrual Cycle